Shear Wave Elastography of Liver: Measurement of normal liver stiffness in healthy population and factors affecting it - Namrita Dhar; Dr. Ishan Gupta; Kulbhushan Gupta (International Journal of Medical Research and Review, 2022)
Background: Shear Wave Elastography (SWE) is a recent non-invasive method for determining liverstiffness. SWE is a two-dimensional elastography technique in which an amplitude-modulated beamof focused ultrasound is used to generate shear waves which are then transmitted by the transducerto the region of interest (ROI), where the propagation speed of shear waves is measured. Thepresent study is the first attempt to measure the normal range of liver stiffness using SWE in ahealthy population from North India and to study the effect of age, gender, and BMI on the liverstiffness values in the healthy population.Methods: This cross-sectional observational study wasconducted in the Department of Radiodiagnosis and Imaging, Government Medical College, Jammuon 117 healthy subjects without any known liver pathology or history of any liver disease. B-ModeUltrasound scan, followed by SWE Examination was performed on all subjects using SAMSUNGRS80EVO using CA1-7A convex array probe with a frequency of 1 to 7 MHz.Results: Successfulresults were obtained in 98.2%. The mean value of liver stiffness in 115 healthy subjects was 4.74± 0.91 kPa, and the 95% confidence interval was 4.58-4.91 kPa. (Range: 2.7-7.8 kPa). There wereno statistically significant differences in liver stiffness values regarding age, gender and BMI in thehealthy population (all p> 0.05).